Dinamika Inovasi Badan Usaha Milik Pondok (BUMP) Pondok Lirboyo dalam Pemberdayaan Wirausaha Alumni dan Peningkatan Kesejahteraan Sosial Masyarakat - Wafa, Fadhil; Prasetiyo, Luhur (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to examine the dynamics of innovation within the Islamic Boarding School-Owned Enterprise (BUMP) of Lirboyo Islamic Boarding School in the process of empowering alumni entrepreneurs and its contribution to improving the social welfare of the community. The phenomenon of BUMP Islamic boarding schools developing into business-community entities demonstrates a new paradigm shift from religious institutions to community-based entrepreneurial institutions that simultaneously integrate spiritual, economic, and social values. This study seeks to uncover how institutional innovation, business model innovation, and empowerment strategy innovation implemented by BUMP continuously undergo adaptive transformation to market dynamics, community-based economic opportunities, and the economic empowerment needs of alumni engaged in various business sectors. The research approach is qualitative with a grounded structure that explores the processes, patterns of change, mechanisms of innovation action, and social meanings formed within the alumni network and institutional relationships of BUMP. The research findings are expected to explain how the social and business innovations developed by BUMP Pondok Lirboyo act as catalysts for the formation of an Islamic boarding school-based business ecosystem, which systematically enhances the role of alumni as empowered economic agents and contributes to improving the social welfare of the community. This research provides theoretical contributions to the development of social-enterprise-based Islamic boarding school institutional studies, as well as practical contributions to the formulation of policy models and strategies for strengthening a sustainable alumni entrepreneurial ecosystem based on social innovation. In the long term, this research confirms that the dynamics of innovation managed within the Islamic boarding school institutional system not only serve as a driver of community economic growth but also serve as a mechanism for social value creation that strengthens the community’s economic resilience, enhances alumni entrepreneurial capabilities,